Compression stockings do not improve muscular performance during a half-ironman triathlon race - Del Coso, J.; Areces, F.; Salinero, J. J.; Gonzalez-Millan, C.; Abian-Vicen, J.; Soriano, L.; Ruiz, D.; Gallo, C.; Lara, B.; Calleja-Gonzalez, J. (European Journal of Applied Physiology, 2014)
Purpose This study aimed at investigating the effectiveness of compression stockings to prevent muscular damage and preserve muscular performance during a half-ironman triathlon. Methods Thirty-six experienced triathletes volunteered for this study. Participants were matched for age, anthropometric data and training status and placed into the experimental group (N = 19; using ankle-to-knee graduated compression stockings) or control group (N = 17; using regular socks). Participants competed in a half-ironman triathlon celebrated at 29 ± 3 °C and 73 ± 8 % of relative humidity. Race time was measured by means of chip timing. Pre- and post-race, maximal height and leg muscle power were measured during a countermovement jump. At the same time, blood myoglobin and creatine kinase concentrations were determined and the triathletes were asked for perceived exertion and muscle soreness using validated scales. Results Total race time was not different between groups (315 ± 45 for the control group and 310 ± 32 min for the experimental group; P = 0.46). After the race, jump height (-8.5 ± 3.0 versus -9.2 ± 5.3 %; P = 0.47) and leg muscle power reductions (-13 ± 10 versus -15 ± 10 %; P = 0.72) were similar between groups. Post-race myoglobin (718 ± 119 versus 591 ± 100 ?g/mL; P = 0.42) and creatine kinase concentrations (604 ± 137 versus 525 ± 69 U/L; P = 0.60) were not different between groups. Perceived muscle soreness (5.3 ± 2.1 versus 6.0 ± 2.0 arbitrary units; P = 0.42) and the rating of perceived effort (17 ± 2 versus 17 ± 2 arbitrary units; P = 0.58) were not different between groups after the race. Conclusion Wearing compression stockings did not represent any advantage for maintaining muscle function or reducing blood markers of muscle damage during a triathlon event.